2016
DOI: 10.2337/dc16-0089
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Meal-Related Glycemic Excursions in an Insulin-Sparing Manner During Closed-Loop Insulin Delivery: The Beneficial Effects of Adjunctive Pramlintide and Liraglutide

Abstract: OBJECTIVEClosed-loop (CL) insulin delivery effectively maintains glucose overnight but struggles when challenged with meals. Use of single-day, 30-μg/meal pramlintide lowers meal excursions during CL. We sought to further elucidate the potential benefits of adjunctive agents after 3–4 weeks of outpatient dose titration.RESEARCH DESIGN AND METHODSTwo CL studies were conducted: one evaluating adjunctive pramlintide and the other liraglutide. Ten subjects (age 16–23 years; A1C 7.2 ± 0.6% [55 ± 6.6 mmol/mol]) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 26 publications
3
55
0
1
Order By: Relevance
“…It is hoped that CLS will alleviate several day‐to‐day burdensome tasks for patients, including simplifying meal insulin bolus calculation . Fully‐automated CLSs have failed to provide adequate post‐meal glucose control, although promising and interesting avenues are being investigated, such as the intraperitoneal insulin delivery route or concomitant use of pramlintide . Faster acting insulins also improve the performance of CLS and should be further explored to simplify meal insulin bolus calculation.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that CLS will alleviate several day‐to‐day burdensome tasks for patients, including simplifying meal insulin bolus calculation . Fully‐automated CLSs have failed to provide adequate post‐meal glucose control, although promising and interesting avenues are being investigated, such as the intraperitoneal insulin delivery route or concomitant use of pramlintide . Faster acting insulins also improve the performance of CLS and should be further explored to simplify meal insulin bolus calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies focused on demonstrating feasibility of automated insulin delivery in carefully controlled in‐clinic studies, and were conducted in a range of patients including children, adolescents, adults, and in pregnant women . These included single hormone, dual hormone systems, and the incorporation of insulin absorption adjuncts . In‐clinic studies that simulated hypothetical real world challenges including exercise, alcohol, high fat meals, and inaccurate continuous glucose sensors followed, and demonstrated that the automated insulin delivery systems remained safe and effective.…”
Section: Closed Loop Systemsmentioning
confidence: 99%
“…Dual-hormone systems are also being explored, whether it be through the addition of glucagon in hopes of more closely approximating normal physiological function by infusing glucagon when sensor glucose levels trend low or through the addition of other adjunctive therapies, such as pramlintide or liraglutide (26,39,40).…”
Section: New Features To Promote Hcl Use In Pediatricsmentioning
confidence: 99%